Burden of Dengue–Typhoid Coinfection in Pediatric Patients: A 6-year Experience from a Tertiary Care Center - Aravinda Anjana; Ranjeeta Adhikary; Malavalli V Bhavana (Pediatric Infectious Disease)
Background: India is endemic to both typhoid and dengue, which also mimic in their clinical presentations. This poses a diagnostic dilemma especially for pediatric patients. Literature on such coinfections is limited. Methodology: We retrospectively analyzed six years data (2017–2022). All pediatric culture proven typhoid cases with concurrent dengue infection were included in the study. Patient clinical and demographic profiles were extracted from the hospital information system. Results: We report four such cases of coinfection. Along with the expected reduced platelet counts, most of the patients had associated deranged TLC, liver enzymes, hypoalbuminemia and gallbladder changes. Conclusion: Our study contributes to the body of literature on dengue–typhoid coinfection in pediatric patients and the pitfall in accepting a single pathogen etiology. Awareness needs to be raised among healthcare workers on the potential dengue–typhoid coinfection, especially in endemic countries.